The contemporary problem of style - Richard Robinson (Textual Practice, 2022)
This essay sets the parameters of this special issue on the contemporary problem of style. Noting that the critical term style has returned to discursive prominence in recent years, this introduction explores the peculiarity of its status in literary studies. Asking how style underlies critical practice today, we track the partially conflicting genealogies of style and the variety of its disciplinary relations. We explore the problem of style now: in its modernist inheritances; its association to class and nationality, especially Englishness; its reconfiguration through world Englishes and the global novel; its coupling with new aestheticism and new formalism; its recasting as a problem of receptivity and attachment in the era of ‘post-critique’; its intimate connection to shame, affect and embodiment (given especial impetus by critical race theory and sexuality studies); and its persistent association with subcultures and the scandalous pleasures of ‘lifestyle’.